3.1 Ga crystallization age for magnesian and ferroan gabbro lithologies in the Northwest Africa 773 clan of lunar meteorites. (15th September 2017) - Shaulis, B.J.; Righter, M.; Lapen, T.J.; Jolliff, B.L.; Irving, A.J.
Abstract: The Northwest Africa (NWA) 773 clan of meteorites is a group of paired and/or petrogenetically related stones that contain at least six different lithologies: magnesian gabbro, ferroan gabbro, anorthositic gabbro, olivine phyric basalt, regolith breccia, and polymict breccia. Uranium-lead dates of baddeleyite in the magnesian gabbro, ferroan gabbro, and components within breccia lithologies of paired lunar meteorites NWA 773, NWA 3170, NWA 6950, and NWA 7007 indicate a chronologic link among the meteorites and their components. A total of 50 baddeleyite grains were analyzed and yielded weighted average 207 Pb- 206 Pb dates of 3119.4 ± 9.4 ( n  = 27), 3108 ± 20 ( n  = 13), and 3113 ± 15 ( n  = 10) Ma for the magnesian gabbro, ferroan gabbro, and polymict breccia lithologies, respectively. A weighted average date of 3115.6 ± 6.8 Ma ( n  = 47/50) was calculated from the baddeleyite dates for all lithologies. A single large zircon grain found in a lithic clast in the polymict breccia of NWA 773 yielded a U-Pb concordia date of 3953 ± 18 Ma, indicating a much more ancient source for some of the components within the breccia. A U-Pb concordia date of apatite and merrillite grains from the magnesian gabbro and polymict breccia lithologies in NWA 773 is 3112 ± 33 Ma, identical to the baddeleyite dates. Magnesian and ferroan gabbros, as well as the dated baddeleyite and Ca-phosphate-bearing detritus in the breccia lithologies, formed during the same igneous event at about 3115 Ma. These data also strengthen proposed petrogenetic connections between magnesian and ferroan gabbro lithologies, which represent some of the youngest igneous rocks known from the Moon.